To Assess the Iron Reserves in Blood Donors by Measuring Serum Ferritin and Hemoglobin in the Children Hospital Lahore - Tooba Fateen, Sehar Shamshad Ali, Nazish Saqlain, Faiza Shafqat, Ayesha Khalid, Kanwar Sajid Ali, Zertaj Kashif (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Frequent contribution of blood can cause iron exhaustion in blood donors along with the problems related to it. Curtailing the proportion of iron reduction among blood donors is a crucial plan for boosting donor’s well-being. Aim & objectives: The aim of this analysis is to determine iron stocks by measuring serum ferritin in pre-donation male blood donors along with their relation with the hemoglobin concentration and frequency of blood donations. Study design: Cross-sectional study. Place and duration: Pathology (immunohematology) department and blood bank of University of Child Health Sciences, The Children Hospital Lahore from Aug 2021 to July 2022 Material and Methods: A total of 350 serum samples were processed to determine hemoglobin and serum ferritin concentrations. The study involved was performed on healthy blood donors. The method used was chemiluminescence for the simultaneous measurement of serum ferritin. Results: An aggregate of 350 serums were collected from the contributors in blood bank. Among them, 154 were the first-time donor and 196 were the frequent donors; the serum ferritin was markedly reduced in constant contributors. The mean value 105ng/mL was found in infrequent donors and 79.35ng/mL was found in frequent donors. There was no notable variance in hemoglobin of newbie and regular blood givers. However, a momentous variation in the pervasiveness of iron depletion between first‑time and regular donors is found. Conclusion: Blood donation has a noteworthy impact on iron stores and is one of the most important factors for iron shortage in contributors, specifically in those who donate blood again and again. Serum ferritin measurement ought to be incorporated in the blood donor preference especially in the evaluation of consistent blood givers to assure enough iron pools in the donor community in order to sustain a pertinent potential donor.